Scoping Literature Review of STEM Research in Indonesia in Improving Critical Thinking Skills and Concepts Mastery - Pradnya Parameswari; Suyatno Sutoyo; Utiya Azizah (Indonesian Journal Of Educational Research and Review, 2023)
The publication of previous articles on STEM research was still limited to describing the impact of STEM on learning and did not provide specific information on certain competencies. In addition, these publications are still limited to one level of education and subjects as sample criteria. This study aims to analyze the literature on STEM research in Indonesia in improving critical thinking skills and concepts mastery in chemistry, physics, biology, and science subjects from elementary to tertiary education levels, summarizing and disseminating a wide selection of literature. Research methods include identifying research questions, identifying relevant studies by searching for research articles in journals and conference articles in proceedings with certain keywords, selecting studies based on criteria, mapping data, then compiling, summarizing, and reporting the results. After that charting the data is synthesizing and interpreting qualitative data by sifting, charting, and sorting material according to key issues and themes. The findings from this analysis are that STEM research is dominated by the use of experimental methods (53.33%), STEM as a learning approach (71.1%), and especially PjBL (24.44) and PBL (17.78%). STEM research related to learning and developing learning tools based on learning models other than PjBL and PBL has not been done much.